Identification and characterization of immunoglobulin tau (IgT) in Asian Seabass (Lates calcarifer) and mucosal immune response to nervous necrosis virus - Chan, Janlin; Carmen, Lee Ching Pei; Lee, Si Qi; Prabakaran, Mookkan (Frontiers in Immunology, 2023)
Mucosal immunity plays a critical role in the protection of teleost fish against infection, but mucosal immunoglobulin of important aquaculture species unique to Southeast Asia remained greatly understudied. In this study, the sequence of immunoglobulin T (IgT) from Asian sea bass (ASB) is described for the first time. IgT of ASB possesses the characteristic structure of immunoglobulin with a variable heavy chain and four CH4 domains. The CH2-CH4 domains and full-length IgT were expressed and CH2-CH4 specific antibody was validated against full-length IgT expressed in Sf9 III cells. Subsequent use of the anti-CH2-CH4 antibody in immunofluorescence staining confirmed the presence of IgT-positive cells in the ASB gill and intestine. The constitutive expression of ASB IgT was characterized in different tissues and in response to red-spotted grouper nervous necrosis virus (RGNNV) infection. The highest basal expression of secretory IgT (sIgT) was observed in the mucosal and lymphoid tissues such as the gills, intestine and head kidney. Following NNV infection, IgT expression was upregulated in the head kidney and mucosal tissues. Moreover, a significant increase in localized IgT was found in gills and intestines of infected fish on day 14 post-infection. Interestingly, a significant increase in NNV-specific IgT secretion was only observed in the gills of the infected group. Our results suggest that ASB IgT may play an important role in the adaptive mucosal immune responses against viral infection and could potentially be adapted as a tool for the evaluation of prospective mucosal vaccines and adjuvants for the species.